Prevention of Venous Thromboembolism in Hospitalized Medically Ill Patients: A U.S. Perspective - Spyropoulos, Alex C.; Ageno, Walter; Cohen, Alexander T.; Gibson, C. Michael; Goldhaber, Samuel Z.; Raskob, Gary (Thrombosis and Haemostasis, 2020)
Venous thromboembolism (VTE) remains a major cause of morbidity and mortality in hospitalized medically ill patients. These patients constitute a heterogeneous population, whose VTE risk is dependent upon the acute medical illness, immobility status, and patient-specific risk factors that have been incorporated into individualized VTE risk assessment models. Randomized placebo-controlled trials (RCTs) have shown both efficacy and net clinical benefit of in-hospital thromboprophylaxis, which is supported by guideline recommendations. The data for extended posthospital discharge thromboprophylaxis are more nuanced. RCTs comparing standardized duration low-molecular weight heparin versus extended duration direct oral anticoagulants, such as betrixaban and rivaroxaban, have shown efficacy and net clinical benefit in select groups of high VTE and low-bleed risk populations of hospitalized medically ill patients. These oral agents are now approved for both in-hospital and extended thromboprophylaxis. However, the most recent guidelines do not recommend routine use of these agents for extended thromboprophylaxis. Longitudinal studies in medically ill patients have shown that the majority of VTE events occur in the posthospital discharge setting within 6 weeks of hospitalization. This, coupled with the short hospital length-of-stay and lack of routine postdischarge thromboprophylaxis in U.S. health care settings, has dampened quality improvement efforts aimed at reducing hospital-acquired VTE. The aim of this multidisciplinary document is to provide an evidence-based framework to guide clinicians in assessing VTE and bleeding risk in hospitalized medically ill patients using an individualized, risk-adapted, and patient-centered approach, with the aim of providing clinical pathways toward the use of appropriate type and duration of available thromboprophylactic agents.
Keywords: venous thromboembolism; medically ill; extended thromboprophylaxis; heparin; direct oral anticoagulants